A prospective study of the palpable lesions of the breast and the role of FNAC in these lesions with available histopathology methods - Dr. Arzeena Kaleemuddin; Dr. K. Suresh; Dr. Mohan Reddy; Dr. Florence Nightingale (Tropical Journal of Pathology and Microbiology)
Introduction: Benign as well as malignant breast lesions are quite common in Indian population. It is the second most common cancer site after cancer cervix. Fine-needle aspiration cytology (FNAC) is safe, reliable, and time saving outdoor procedure with little discomfort to the patient. Objective: The current study was aimed to study the frequency of various breast lesions on FNAC in a tertiary care center and its histopathological correlation. Methodology: Total of 217 cases of FNAC was conducted in the palpable lesions of the breast. Result: Most of the lesions were noted in the left breast (123) lesions out of which 29 were malignant. The various benign neoplastic lesions seen were 81 patients. Fibroadenoma were found mostly in the age group of 21-30 years. 41 cases of fibrocystic disease found mostly in the age group of 31 to 50 years. The lymph node metastasis was seen in 5 patients with 35 to 55yrs of age. There were 71 benign neoplastic lesions and 21 cases of malignancy available for histopathology. FNAC was 80.9% sensitive and 95.89% specific in diagnosing malignant lesions. Conclusion: A high sensitivity and a high positive predictive value proved that a positive FNAC in the breast means a definite diagnosis of the concerned pathology if compared with the final histology report. Thus, we have no hesitation in concluding that FNAC is a very important preliminary diagnostic test in palpable breast lumps and done by expert hands, the results show a high degree of correlation with the final histopathology report.